Educación financiera y manejo de finanzas personales en el segmento jóvenes del cantón Loja - Lozano Alvarado, Ronaldo David (2022)
Financial knowledge is a distinguished factor in improving management skills and achieving financial freedom. The research objective is to develop a financial education and personal finance program aimed at the young segment of the Loja canton. The study is kind of a descriptive type, as an information collection instrument, a survey based on the PISA test (Programme for International Student Assessment) was obtained, which allows classifying the financial knowledge level that the respondents possess, the population study was made up by 381 young people between 20 and 29 years old belonging to the Loja canton, stratified into 320 in the urban area and 61 in the rural area. The results show specially the general population has a saving habit and plans their finances, in the same way, they have level five in financial knowledge, for this reason they are able to analyze complex financial products and understand a wide range of financial terms and concepts; a didactic guide was developed which allowed the knowledge development in young people focused on the basic pillars of financial education; After the training days, greater financial knowledge is revealed in the population, ranking at level 5, considering the standardization of the PISA Test, thus demonstrating better skills that make it possible to make efficient financial decisions.